Creep - Hillier, Jennifer (New York : Gallery Books, 2011)
Dr. Sheila Tao is a professor of psychology. An expert in human behavior. And when she began an affair with sexy, charming graduate student Ethan Wolfe, she knew she was playing with fire. Consumed by lust when they were together, riddled with guilt when they weren't, she sknows the three-month fling with her teaching assistant has to end. After all, she finally engaged to a kind and loving investment banker who adores her, and she's taking control of her life. But when she attempts to end the affair, Ethan Wolfe won't let her walk away.
edited hb 2015-06-16
Keywords: Extortion -- Fiction; Women college teachers -- Fiction; Psychological fiction; Suspense fiction